Validation of hearing handicap inventory for elderly-screening among elderly in Seremban, Malaysia - Camarudin, Noraini (2019)
A diminished ability to hear and communicate with other individuals related to sensory-neural hearing loss among the elderly will lead to negative well-being, poor quality of life and increased risk of mortality. The importance of early detection of hearing impairment and further management from experiencing serious impact could increase their quality of life. Pure tone audiometry (PTA) is the formal audiometric and standard test used to assess the level of impairment of hearing with different frequency tests to classify the level of hearing. Alternatively, the Hearing Handicap Inventory for the elderly-screening (HHIE-S) is one instrument commonly used for hearing questionnaires aimed as a screening tool used to detect the level of hearing handicap by the elderly. Although the original HHIE-S assessed social and emotional factors associated with hearing impairment, it has also been used to screen individual hearing levels. Limited accessibility to the hearing screening tool at the primer health care setting led the elderly with problem hearing impairment under detection. The limited number of PTA services in primary health care therefore the effective, sensitive, valid, basic and inexpensive hearing screening tools are required to detect hearing impairment in a large scale among elderly subjects in primary settings or hospitals where PTA tests are not available. The aim of the study is to determine the validity of the use of the HHIE-S score for measured hearing handicap and compared with the PTA result. This is a cross-sectional study was carried out among the elderly aged 60 years and above randomly selected at Audiology Unit, in Tuanku Ja’afar Hospital, Negeri Sembilan between August and November 2018. Respondents were consecutively selected based on the study inclusion and exclusion comprising socio-demographic characteristic, HHIE-S questionnaire. The PTA results from the best hearing taken from the patient report where the procedure was done by an Audiologist. Logistic regression analysis was used to analyze the association between the variables. Total HHIE-S scores and the formal audiometric test were explored with sensitivity, specificity and predictive value, while the correlation coefficient combines HHIE-S scores and PTA test. It involved 202 participants in this study by completing the questionnaire and doing PTA assessment. For the validity of the HHIE-S questionnaire, the HHIES score was compared with the PTA result the sensitivity was 87.9%, specificity was 78.4%, positive predictive value (PPV) was 80.3% and negative predictive value (NPV) was 86.6%. This study found the prevalence of hearing handicap measured by HHIE-S score was 75.7% and hearing impairment from PTA result was 81.7%. The HHIE-S score among the elderly were significant association with age, gender, usage of hearing aids for socio-demographic and the level of hearing impairment measured by PTA (r=0.704, p<0.001). For the conclusion, this study highlighted the use of HHIE-S for hearing screening instruments for primary care prevention. The HHIE-S questionnaire appears a good screening instrument among the elderly with valid screening parameters when compared with the PTA. The advantages of the HHIE-S questionnaire as a screening tool can be used at the community level to detect the elderly with hearing impairment on a large scale. The HHIE-S questionnaire is recommended for use as a basic hearing screening instrument for elderly at the health clinic or hospital where PTA service is not available.